Survei Kemenarikan Taman Margasatwa Ragunan bagi Pengunjung - Subakdi; Satino; Suprima; Ahmad Hidayatullah; Farchanza Haykanna Pireno; Fitrya Putry Amanda (Syntax Idea, 2067)
Ragunan Margasatwa Park is one of the forms of industrial and tourism acceleration in Indonesia. To this day the Ragunan Margasatwa Park is still operating well and has its own heritage in it. This is why Ragunan Margasatwa Park remains a favourite destination for recreation with family or close people. In order to obtain real data or evidence of the creation that exists within Ragunan Margasatwa Park, researchers will conduct surveys to the visitors by informing the activities that the researchers do through poster products. In order to find out what is of interest to visitors so choose Ragunan Margasatwa Park as their recreational destination. The results of the research we have done have produced the average level of satisfaction of Ragunan Margasatwa Park for visitors on a scale of 5 which is Very Satisfied / Very Interesting. The result of the spread of the lift, will later be the advocate of the truth of the data in the product of the article that the researchers sorted. In addition, the results of the spread of the lift also become factual data that will be informed by the researchers through video products.